Resumindo e concluindo... Yes, we QAM - Sílvio Almeida Abrantes Moreira (2009)
The main properties of the hybrid modulation QAM are addressed in this text. We will see how to modulate and demodulate a QAM signal and how to predict the modulation performance in terms of error probabilities.